Editorial - Pedro Soares Neves (Architecture Image Studies Scientific Journal)
Welcome to the latest issue of AIS, where we delve into the fascinating realms of design, restoration, and place-making within the architectural landscape. In this edition, we present a collection of insightful articles that explore diverse aspects of architectural interventions, from urban parks to waterside mansions, participatory urban place-making, dog parks, and the evolution of interior design in 19th-century Ottoman architecture.